2017
DOI: 10.1002/pro.3286
|View full text |Cite
|
Sign up to set email alerts
|

Engineered, highly reactive substrates of microbial transglutaminase enable protein labeling within various secondary structure elements

Abstract: Microbial transglutaminase (MTG) is a practical tool to enzymatically form isopeptide bonds between peptide or protein substrates. This natural approach to crosslinking the side-chains of reactive glutamine and lysine residues is solidly rooted in food and textile processing. More recently, MTG's tolerance for various primary amines in lieu of lysine have revealed its potential for site-specific protein labeling with aminated compounds, including fluorophores. Importantly, MTG can label glutamines at accessibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Particularly, microbial TGase has been utilized in the processing of food products containing meat, fish, dairy, and wheat (Buchert et al, ; Motoki & Seguro, ). Moreover, TGase has been utilized in nonfood industries, such as protein engineering, textile and leather processing, pharmaceutical industries, and development of surgical materials (Fontana, Spolaore, Mero, & Veronese, ; Y. Liu et al, ; Rachel, Quaglia, Levesque, Charette, & Pelletier, ; Zhu & Tramper, ). Among the many microbial TGases that have been studied for their expression and activity in Escherichia coli , Streptomyces mobaraensis TGase (Sm TGase) is the first industrial enzyme (Kawai, Takehana, & Takagi, ; Pasternack et al, ; Yokoyama, Nakamura, Seguro, & Kubota, ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, microbial TGase has been utilized in the processing of food products containing meat, fish, dairy, and wheat (Buchert et al, ; Motoki & Seguro, ). Moreover, TGase has been utilized in nonfood industries, such as protein engineering, textile and leather processing, pharmaceutical industries, and development of surgical materials (Fontana, Spolaore, Mero, & Veronese, ; Y. Liu et al, ; Rachel, Quaglia, Levesque, Charette, & Pelletier, ; Zhu & Tramper, ). Among the many microbial TGases that have been studied for their expression and activity in Escherichia coli , Streptomyces mobaraensis TGase (Sm TGase) is the first industrial enzyme (Kawai, Takehana, & Takagi, ; Pasternack et al, ; Yokoyama, Nakamura, Seguro, & Kubota, ).…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of conditions for metabolic incorporation of TePhe into His 6 -GB1 in E. coli N-terminally his-tagged GB1 (His 6 -GB1) was expressed from a pET15b plasmid (generous gift of Prof. Joelle Pelletier) [28] in BL21 (DE3) E. coli. This construct contains a thrombin site following the his-tag which when cut leaves a Gly-Ser-His leader prior the start methionine of GB1 (see Supporting Information for full sequence).…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme catalyzes an acyl transfer reaction at certain glutamine side chains, where the acyl group can be transferred to various primary amines for conjugation or to water in a competing hydrolysis reaction. The exact sequence and structural requirements for the glutamine substrate are still under investigation. In terms of the amine substrate, it has been reported that the enzyme poorly tolerates negatively charged substrates including negatively charged polymers, where the enzyme failed to conjugate an amine-terminated oligonucleotide to a classic acyl donor model protein N , N -dimethyl casein. However, the enzyme has been used for modifying a variety of proteins including antibodies and for polymers such as PEG .…”
Section: Results and Discussionmentioning
confidence: 99%